Probing the antisymmetric Fano interference assisted by a Majorana fermion - Dessotti, F. A. [UNESP]; Ricco, L. S. [UNESP]; Souza, M. de [UNESP]; Souza, F. M.; Seridonio, A. C. [UNESP] (Amer Inst Physics, 2014)
As the Fano effect is an interference phenomenon where tunneling paths compete for the electronic transport, it becomes a probe to catch fingerprints of Majorana fermions lying on condensed matter systems. In this work, we benefit of this mechanism by proposing as a route for that an Aharonov-Bohm-like interferometer composed by two quantum dots, being one of them coupled to a Majorana bound state, which is attached to one of the edges of a semi-infinite Kitaev wire within the topological phase. By changing the Fermi energy of the leads and the symmetric detuning of the levels for the dots, we show that opposing Fano regimes result in a transmittance characterized by distinct conducting and insulating regions, which are fingerprints of an isolated Majorana quasi-particle. Furthermore, we show that the maximum fluctuation of the transmittance as a function of the detuning is half for a semi-infinite wire, while it corresponds to the unity for a finite system. The setup proposed here constitutes an alternative experimental tool to detect Majorana excitations. (C) 2014 AIP Publishing LLC.